CONSTRUCTING URGENCY AND SCARCITY IN INDONESIAN SHOPEE FLASH SALE ADVERTISEMENTS: A PRAGMATIC ANALYSIS - beta setiawati (PT Akselerasi Karya Mandiri, 2026)
This study examines the linguistic construction of urgency and scarcity in Shopee flash sale advertisements and their pragmatic functions in shaping consumer perception and decision-making. Using a qualitative descriptive design with a discourse-analytic approach, data were collected from 132 flash sale advertisements over a four-week period. The data were analysed through discourse analysis and pragmatics, focusing on speech acts and implicature. The findings identified 381 linguistic markers, comprising 214 urgency expressions and 167 scarcity expressions. Urgency was mainly expressed through time-bound markers and action prompts, while scarcity was conveyed through stock limitation and quantity indicators. Exclamatory forms, imperative sentences, elliptical phrases, and code-mixing were frequently used to strengthen persuasive effects. Additionally, 64% of the advertisements combined urgency and scarcity strategies, making this the dominant persuasive pattern. Pragmatically, these expressions functioned as indirect persuasive acts that created perceptions of limited time and availability, encouraging immediate consumer action. The study highlights how linguistic choices serve as effective persuasive tools in Indonesian digital marketing discourse.